Families' experiences of grief and bereavement in the emergency department: A scoping review. Issue 1 (7th September 2021) - Ito, Yoshiyasu; Tsubaki, Michihiro; Kobayashi, Masahiro
Abstract: Aim: Death is a frequent event in the emergency department, and many family members experience grief and bereavement. However, little is known about what families experience. The aim of this study was to explore previous findings about families' experiences of grief and bereavement in the emergency department to clarify and understand their experience. Methods: A scoping review was chosen as the design for this research. Studies were searched from four electronic databases. The obtained studies were screened independently by two reviewers and selected by mutual agreement of the entire team based upon the eligibility criteria. All relevant data were extracted, and thematic analysis was conducted to assess families' grief and bereavement experiences in the emergency department. Results: The database searches initially resulted in 982 studies; these were finally narrowed to 20 studies for data extraction. Publication years ranged from 1987 to 2020. The studies were conducted across nine countries; most were from the United States and had a qualitative research design. Analysis elicited the following themes: "lack of information, " "breaking bad news, " "being present during resuscitation, " "chaotic environment, " "psychosocial reaction in bereavement, " and "support and care needs from healthcare professionals." Conclusion: These themes reveal challenges in providing support and care from emergency nurses to bereaved families, including inadequate provision of information, poor design of the emergency department due to the lack of privacy, and families' unmet support and care needs. Emergency nurses need to better understand families' experience of grief and bereavement.